Detection Antibodies IgM, IgG and Determination Levels of IL-33 in Iraqi Diabetic Type 2 Patients Infected with Toxoplasma Gondii - Sarah Ali Saeed1 , Israa Kasim Al-Aubaidi2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Toxoplasma gondii is an obligate intracellular protozoan that causes a disease called toxoplasmosis which has the capability to pass its both life cycle parts asexual and sexual in the final host (cats)and also through intermediate vertebrate hosts including humans. Diabetes mellitus is a metabolic disorder that there is high blood sugar level over a prolonged period. This research included one hundred and twenty blood samples that collected from diabetic patients after diagnosing them by endocrinologist at the Imamein Kadhimein Medical City during August until the end of December 2016 with age ranging 12-76 years with mean 50.9 ± 13.8. Toxoplasmosis diagnoses was occurred by using Toxo IgG and IgM antibodies immulite torch assay while diabetes diagnosis by fasting blood sugar tests also measuring level of IL-33 in samples was done by sandwich ELISA method that showed a group of diabetic patients infected with toxoplasmosis have the highest level of IL-33. The results showed that a group of diabetic patients have the highest level of glucose in diabetes test (188.31 pg/ml)while a group of diabetic patients infected with toxoplasmosis have the highest level of IgG (106.17 IU/ml)while all samples have seronegative results for Toxo IgMalso the highest level of IL-33 showed ina group of diabetic patients infected with toxoplasmosis (858.84 pg/ml) while a group of diabetic patients not infected with toxoplasmosis have (556.67 pg/ml) and control group have (315.58pg/ml).